Applying Zero Waste Management Concept in a City of Indonesia: A Literature Review - Nizar, Muhammad; Munir, Erman; Munawar, Edi; ., Irvan; Waller, Vivienne (International Journal of Engineering and Technology, 2019)
City waste management in Indonesia still faces loads of challenges, mainly in the case the ultimate disposal (landfill) availability. Only 60-70% of the waste can be transported and disposed of to landfill, while the rest are scattered in various places. Waste dumped in landfill emits leachate contaminating and greenhouse gases. Also, the discarded material is a waste of non-renewable natural resource. Holistic management is necessary, starting upstream to downstream waste management. The concept of Zero Waste offers waste management, initial from the avoiding of trash, recycling, reduction and recovery of second-hand material. Some cities in the world such as Canberra, Adelaide (Australia), Stockholm (Sweden), Nova-Scotia (Canada) and San Francisco (USA) has set a target of Zero Waste. Indonesia still implements management that emphasizes the waste management disposal in a landfill. This literature review examines to find out whether Indonesia can apply the concept of Zero Waste in the upcoming.Â